2014
DOI: 10.1016/j.ymgmr.2014.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Plasma mutant α-galactosidase A protein and globotriaosylsphingosine level in Fabry disease

Abstract: Fabry disease is an X-linked genetic disorder characterized by deficient activity of α-galactosidase A (GLA) and accumulation of glycolipids, and various GLA gene mutations lead to a wide range of clinical phenotypes from the classic form to the later-onset one. To investigate the biochemical heterogeneity and elucidate the basis of the disease using available clinical samples, we measured GLA activity, GLA protein and accumulated globotriaosylsphingosine (Lyso-Gb3), a biomarker of this disease, in plasma samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 44 publications
2
23
0
Order By: Relevance
“…The aim of the study was to analyze GLA mutations in‐depth on the basis of a holistic approach involving in vitro enzyme activity measurement of the mutant α‐gal A enzyme in cell culture (over‐expression) as well as determination of the biomarker globotriaosylsphingosine (lyso‐Gb3) from either plasma or dried blood spots (DBS). Lyso‐Gb3 is a deacylated metabolite of Gb3 with a higher sensitivity than Gb3 and a good correlation to the FD phenotype [Tsukimura et al., , Smid et al., (II)]. Furthermore, we introduce outline data for 61 male and 116 female patients with atypical FD (including age of diagnosis and symptomatic spectrum) in concurrence with one of 26 GVUS described in this study, in an attempt to elucidate the pathogenesis of these specific cases.…”
Section: Introductionmentioning
confidence: 80%
“…The aim of the study was to analyze GLA mutations in‐depth on the basis of a holistic approach involving in vitro enzyme activity measurement of the mutant α‐gal A enzyme in cell culture (over‐expression) as well as determination of the biomarker globotriaosylsphingosine (lyso‐Gb3) from either plasma or dried blood spots (DBS). Lyso‐Gb3 is a deacylated metabolite of Gb3 with a higher sensitivity than Gb3 and a good correlation to the FD phenotype [Tsukimura et al., , Smid et al., (II)]. Furthermore, we introduce outline data for 61 male and 116 female patients with atypical FD (including age of diagnosis and symptomatic spectrum) in concurrence with one of 26 GVUS described in this study, in an attempt to elucidate the pathogenesis of these specific cases.…”
Section: Introductionmentioning
confidence: 80%
“…Patients with this mutation have residual GLA activity, and usually manifest no childhood symptoms, such as acroparesthesia, angiokeratomas, hypohidrosis, or corneal opacities, but develop renal and/or cardiac disease [ 12 , 29 ]. Previous examinations revealed that the plasma lyso-Gb3 concentrations in male patients with R112H and M296I were below or near the limit of determination [ 7 , 8 , 12 , 30 ]. However, our new sensitive method allowed successful determination of the lyso-Gb3 concentrations in such patients.…”
Section: Discussionmentioning
confidence: 99%
“…For measurement of GLA activity in leukocytes, 10 μl of a leukocyte homogenate (about 10 μg protein) was mixed with 40 μl of the substrate solution in a 1.5 mL micro-tube, followed by incubation at 37 °C for 30 min [ 20 , 23 ]. Then, the reaction was stopped by adding 950 μL of the stopping solution, and the released MU was measured using a spectrofluorometer (F2700; Hitachi Ltd., Tokyo, Japan) at excitation and emission wavelengths of 365 nm and 450 nm, respectively.…”
Section: Methodsmentioning
confidence: 99%